The Effect of Spinal Cord Injury on Beta-Amyloid Plaque Pathology in TgCRND8 Mouse Model of Alzheimer’s Disease - Yuan, Qiuju; Yang, Jian; Xian, Yan-Fang; Liu, Rong; Chan, Chun W.; Wu, Wutian; Lin, Zhi-Xiu (Current Alzheimer Research, 2020)
Background: The accumulation and aggregation of Aβ as amyloid plaques, the hallmark pathology of the Alzheimer's disease, has been found in other neurological disorders, such as traumatic brain injury. The axonal injury may contribute to the formation of Aβ plaques. Studies to date have focused on the brain, with no investigations of spinal cord, although brain and cord share the same cellular components. Objective: We utilized a spinal cord transection model to examine whether spinal cord injury acutely induced the onset or promote the progression of Aβ plaque 3 days after injury in TgCRND8 transgenic model of AD. Methods: Spinal cord transection was performed in TgCRND8 mice and its littermate control wild type mice at the age of 3 and 20 months. Immunohistochemical reactions/ELISA assay were used to determine the extent of axonal damage and occurrence/alteration of Aβ plaques or levels of Aβ at different ages in the spinal cord of TgCRND8 mice. Results: After injury, widespread axonal pathology indicated by intra-axonal co-accumulations of APP and its product, Aβ, was observed in perilesional region of the spinal cord in the TgCRND8 mice at the age of 3 and 20 months, as compared to age-matched non-TgCRND8 mice. However, no Aβ plaques were found in the TgCRND8 mice at the age of 3 months. The 20-month-old TgCRND8 mice with established amyloidosis in spinal cord had a reduction rather than increase in plaque burden at the lesion site compared to the tissue adjacent to the injured area and corresponding area in sham mice following spinal cord transection. The lesion site of spinal cord area was occupied by CD68 positive macrophages/ activated microglia in injured mice compared to sham animals. These results indicate that spinal cord injury does not induce the acute onset and progression of Aβ plaque deposition in the spinal cord of TgCRND8 mice. Conversely, it induces the regression of Aβ plaque deposition in TgCRND8 mice. Conclusion: The findings underscore the dependence of traumatic axonal injury in governing acute Aβ plaque formation and provide evidence that Aβ plaque pathology may not play a role in secondary injury cascades following spinal cord injury.
Keywords: amyloid precursor protein